Oil Spillages and Captured Fish Production in the Niger Delta of Nigeria - Olaifa, Eseoghene S.; Osabuohien, Evans S.; Issahaku, Haruna; Matthew, Oluwatoyin (International Journal of Energy Economics and Policy, 2022)
The Niger Delta is the oil-producing region in Nigeria; it is the largest wetland in Nigeria and among the 10 most important wetland and marine ecosystems globally. The incidence of oil spillages raised serious concerns about seafood safety. Hence, this study empirically examined oil spillages and captured fish production in the Niger Delta of Nigeria. This study used secondary data from 1986 to 2018, which was sourced from the Food and Agricultural Organisation (FAO), Central Bank of Nigeria (CBN), Federal Department of Fisheries (FDF) and Department of Petroleum Resources (DPR). The study engaged Auto-Regressive Distributed Lag (ARDL) Bounds estimation technique. The findings revealed that oil spillages negatively impact fish production in Nigeria at 5% level of significance. The ARDL error correction model (ECM) for the first simulation showed a relatively low value of -0.28. This implies a relatively low speed of adjustment, which captures the rate of return to equilibrium. Therefore, this study concludes that oil spillage decreases the quantity of captured fish production in the Niger Delta region of Nigeria. It is essential that fishing remains viable because it is the main employer in the region. This can be accomplished by sustainable exploitation, utilisation and management of oil resources in the Niger Delta region.